HUMAN FREEDOM AS AN AXIOLOGICAL SENSE OF DEVELOPMENT IN INFORMATIONAL EPOCH - Авксентьєва, Т.Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
In informational epoch human freedom is a major axiological sense of development of Ukrainian society. It is not stabilizing of existent quality, but it allows a person to feel social comfort, protection from despotism. Dualism of vectors of development of freedom consists of that along with political individualism, when individual responsibility and attitude increase on corresponding interests, terms are formed for the new forms of political collectivism: from the lobbying to the networks of mutual aid.